Existence, uniqueness, and estimation of solutions for a set of equations of perturbed motion - Martynyuk, A. A.; Martynyuk-Chernienko, Yu. A. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We propose a regularization procedure for a set of equations of perturbed motion with uncertain values of parameters. Using the comparison principle, we establish conditions for the existence of solutions of the original system and the regularized system.